Influence of egg weight on fertility and hatchability of backyard poultry varieties maintained under institutional farm conditions - PATRA, MANAS KUMAR; SANCHU, VIHIELE; NGULLIE, EBIBENI; HAJRA, D K; DEKA, BIDYUT C (The Indian Journal of Animal Sciences, 2016)
The study was conducted to investigate the effect of egg weight on fertility and hatchability in Vanaraja and Gramapriya chicken at a particular age. Depending on weight of eggs of Vanaraja (592) and Gramapriya (657) varieties, eggs were divided in Gr.1 (large, weight ≥65 g), Gr. 2 (medium, weight ≥52 to